2018
DOI: 10.1159/000492257
|View full text |Cite
|
Sign up to set email alerts
|

Zedoarondiol Attenuates Endothelial Cells Injury Induced by Oxidized Low-Density Lipoprotein via Nrf2 Activation

Abstract: Background/Aims: Zedoarondiol, a sesquiterpene lactone compound, showed an anti-proliferative activity on vascular smooth muscle cells in our previous study. However, whether it has a beneficial effect on endothelial cells injury induced by oxidized low-density lipoprotein (ox-LDL) remains unclear. This study was designed to investigate the protective effect of zedoarondiol on ox-LDL-induced injury of endothelial cells and explored its underlying mechanism. Methods: The protective effect of zedoarondiol on ox-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
3
14
1
Order By: Relevance
“…Our results showed that ox-LDL promoted oxidative stress and decreased the mRNA expression of Nrf2, which is inconsistent with previous reports. In human umbilical vein endothelial cells, ox-LDL treatment increased Nrf2 protein expression [26] and nuclear Nrf2 translocation [27]. This contradiction can be explained by the fact that ox-LDL can induce endothelial senescence [28], accompanied by increased NADPH oxidases and NADPH oxidase-derived ROS [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that ox-LDL promoted oxidative stress and decreased the mRNA expression of Nrf2, which is inconsistent with previous reports. In human umbilical vein endothelial cells, ox-LDL treatment increased Nrf2 protein expression [26] and nuclear Nrf2 translocation [27]. This contradiction can be explained by the fact that ox-LDL can induce endothelial senescence [28], accompanied by increased NADPH oxidases and NADPH oxidase-derived ROS [29].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is an inflammatory disease with infiltration of monocytes and macrophages in the vessel wall [38]. ox-LDL is a potential source of inflammation in atherosclerosis, as ox-LDL promoted secretion and expression of several proinflammatory cytokines, such as IL-1β, IL-6, TNF-α, and MCP-1 in injured HUVECs [39,40]. In addition to being a proinflammatory cytokine, TNF-α is also a promotor of endothelial cell apoptosis in atherosclerosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that the induction of HO-1 can ameliorate cell injury involved in atherogenesis. Zedoarondiol, an active compound extracted from Curcuma zedaria , has been reported to attenuate oxLDL-induced endothelial cell injury and inflammation via upregulation of HO-1 by Nrf2 [79]. Atractylenolide I (AO-I), isolated from Atractylodes macrocephala , inhibits ox-LDL-induced VSMCs migration and inflammatory responses partly in an HO-1-dependent manner [80].…”
Section: Atherosclerosismentioning
confidence: 99%
“…The cells were seeded in a 2 mL volume of media in six-well plates with and without stybenpropol A (12.5, 50, 200 μM) for 24 h, after which 12.5 ng/mL TNF-α was added at 37 °C for 12 h. The collected supernatants were assayed for VCAM-1, ICAM-1, IL-8, and IL-Iβ levels using appropriate ELISA kits, with absorbance at 450 nm measured via microplate reader [37,38].…”
Section: Methodsmentioning
confidence: 99%